Gender and Wage Gap: Cross-Country Analysis - Kayikci, Fazil; Meyer, Daniel; Cstanho, Rui Alexandre; Coban Kayikci, Fatma; Yilmaz, Sema (SAGE PUBLICATIONS INC, 2025)
Although women's educational achievement and human capital have increased, the wage gap persists both in Germany and Turkey. Also, there are many differences in terms of labor market policies for both countries. This study will discuss the current situation within the framework of various wage gap theories and estimate the relationship between an extensive range of human capital, and economic and social characteristics of gender differences in wages for Germany and Turkey. We employ the stochastic frontier approach methodology to calculate a frontier of wages using German Socio-Economic Panel (SOEP) and the Turkish Statistical Institute's (TUIK) Household Research data and Labor Force Research data. The findings of the study strongly suggest that the current frameworks are inadequate, and more comprehensive measures need to be adopted to promote gender equality in the labor market. Policymakers should focus on creating more inclusive and supportive work environments by improving education, offering greater workplace flexibility, ensuring wage transparency, and providing robust legal protections for women. By addressing these systemic issues, both countries can make strides toward reducing the gender wage gap and promoting a more equitable workforce.JEL Classification: C23, E24, J16, J31.
Keywords: labor force participation; gender inequalities; wage inefficiency; EDUCATION; Social Sciences - Other Topics